Automation of loading process equipment industrial companies - Павленко, П.М. (Proceedings of National Aviation University (archive), 2006)
The results of mathematical modeling the process of loading of the metalcutting equipment by theory methods of mass service are submitted. The results are used for construction of the appropriate program module of the automated system technological preparation of manufacture.